1985
DOI: 10.1007/bf00378561
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pocket gopher mounds on a Texas coastal prairie

Abstract: Effects of pocket gopher (Geomys attwateri) mound-building activity on plant community composition and soil nutrient concentrations were investigated in south Texas on both burned and unburned coastal prairie sites. Pocket gophers deposited large amounts of soil which were lower in nutrient content than randomly-collected samples. Above-ground plant biomass was greater around mounds than in random samples mainly because of increased dicots around mounds on the burned area when compared with random samples on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…We found that the cover of grasses was significantly lower on the mounds as it was also detected by Sigler et al, (2011). The disturbance of fossorial rodents can increase the amount of dicots (Spencer et al, 1985). It was found that the amount of litter also decreased on open surfaces, while litter accumulated in grass dominated swards.…”
Section: Discussionmentioning
confidence: 97%
“…We found that the cover of grasses was significantly lower on the mounds as it was also detected by Sigler et al, (2011). The disturbance of fossorial rodents can increase the amount of dicots (Spencer et al, 1985). It was found that the amount of litter also decreased on open surfaces, while litter accumulated in grass dominated swards.…”
Section: Discussionmentioning
confidence: 97%
“…For the most part, their intensity of disturbance in any one landscape has largely relied on proxies, such as population censuses or rough estimates of mound coverage, with 5%-25% being commonly reported numbers (see, e.g., Richens 1966;Turner et al 1973;Grant et al 1980;Hobbs and Mooney 1985;Spencer et al 1985;Huntly and Inouye 1988;Reichman et al 1993). The majority of mounds are too small to distinguish using traditional remote sensing imagery, limiting all research to what is logistically feasible to achieve at the scale of a research plot (i.e., <1 acre).…”
Section: Case Study 4: Pocket Gopher Mound Feature Detection and Imagmentioning
confidence: 99%
“…Huntly and Reichman [1994] present data from a number of studies that show gophers can excavate 40 L (10.6 gal) soil/d in a new habitat (equivalent to 64.8 [Spencer et al, 1985;Andersen, 1987]. At an average bulk density of 1.62 g/cm 3 for NTS soils, deposition by mound production thus ranges from 1775 kg/yr (2 tons/yr) to more than 8875 kg/yr (10 tons/yr).…”
Section: Burrow Volumementioning
confidence: 99%